Peningkatan Kemampuan Menulis Siswa melalui Metode Mind Mapping di SMK Negeri 01 Pendalian IV Koto - Kartika , Engkar; Dahnas , Israr; Suwarsih, Suwarsih (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effectiveness of the mind mapping method in improving students’ writing skills at SMK Negeri 01 Pendalian IV Koto. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection in two cycles. The subjects are 11th-grade students who struggle with developing ideas and organizing their writing systematically. Data were collected through observations, interviews, writing skill tests, and documentation. The findings indicate that applying the mind mapping method significantly enhances students’ writing abilities. In the first cycle, writing skills improved by 20%, while in the second cycle, they increased by 38%. The mind mapping method helps students organize ideas, connect concepts more clearly, and structure their writing more effectively. This study concludes that mind mapping is an effective strategy for enhancing students’ writing skills at the vocational high school level.